K bor'be za delo Lenina vsegda gotovy! - Savostyuk, O; Uspenskiy, B (Советский художник (Soviet Artist), 1969)
Official portrait of Lenin with poster title forming a red bandand around him Original title: К борьбе за дело Ленина всегда готовы! PO-0135